The police and the far right in Greece: a case study of police voting behaviour in Athens - Papanicolaou, Georgios (Crime, law and social change, 2016)
The electoral advance of the far right party of Golden Dawn has left a clear mark on the Greek parliamentary elections of 2012. A less debated aspect of these results involves the extent of the electoral influence of Golden Dawn among police personnel. Using electoral data from two districts in Greece’s capital city, this paper explores the extent of that influence among major front line police units based in those localities. Our analysis obtains clear indications that Golden Dawn’s presence has been much more emphatic among police personnel than among the general public. These results warrant further exploration of this development, particularly in light of the possibility that far-right ideology may influence the character of everyday policing in Greece and the use of police discretion at the detriment of vulnerable or politically undesirable groups.